Study of the Mixture of Rapeseed Oil and Waste Cooking Oil used for Insulation in Transformers - Van Dung, Nguyen; Thi Tuyet Nhung, Nguyen; Vinh Truong, Le (VNU Journal of Science: Mathematics - Physics; Vol 39 No 2DO - 10.25073/2588-1124/vnumap.4778, 2023)
The blend of waste cooking oil and rapeseed oil was studied as an alternative to mineral oil in transformers. Waste cooking oil after filtering, neutralizing and drying was mixed with refined rapeseed oil. The ratio between waste cooking oil and rapeseed oil was determined based on the pour point. Physico-chemical parameters of the oil mixtures were measured according to the ASTM D6871, and the oil mixture was examined in both new and aged conditions. For ageing, the oil mixture was heated at 120 o C for 164 h with an air flow of 5.5 L/h. In addition, the influence of antioxidants on the breakdown voltage and ageing of the oil mixture was also studied. Experimental results showed that the mixture consisting of 15 vol.% of waste cooking oil and 85 vol.% of rapeseed oil met the standards of ASTM D6871. T ert-butylhydroquinone and propyl gallate significantly increased the oxidation stability index, breakdown voltage and ageing resistance of the the oil mixture.